Critical theory and dystopia - McManus, Patricia (Critical theory and contemporary society., 2022)
Bringing the resources of critical theory to bear on the genre of dystopian fiction, this volume demonstrates both the continuing potential of Theodor Adorno's work on literature, and the meaning of dystopia when considered in the light of Adorno's critique of modernity.